2013
DOI: 10.1136/heartjnl-2012-303052
|View full text |Cite
|
Sign up to set email alerts
|

Human non-contrast T1 values and correlation with histology in diffuse fibrosis

Abstract: BackgroundAortic stenosis (AS) leads to diffuse fibrosis in the myocardium, which is linked to adverse outcome. Myocardial T1 values change with tissue composition.ObjectiveTo test the hypothesis that our recently developed non-contrast cardiac magnetic resonance (CMR) T1 mapping sequence could identify myocardial fibrosis without contrast agent.Design, setting and patientsA prospective CMR non-contrast T1 mapping study of 109 patients with moderate and severe AS and 33 age- and gender-matched controls.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
304
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(336 citation statements)
references
References 30 publications
19
304
2
5
Order By: Relevance
“…In contrast to previous studies, we did not observe a significant relationship between aortic valve area, symptomatic status and DMF. 31 This may be explained by the fact that the present study enrolled mainly patients with severe symptomatic AS, whereas the population of the study by Bull et al 31 also involved asymptomatic patients with moderate to severe AS. Several authors post-contrast administration showed high accuracy to identify patients with severe DMF.…”
Section: Myocardial Fibrosis Vs LV Morphology and Functionmentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast to previous studies, we did not observe a significant relationship between aortic valve area, symptomatic status and DMF. 31 This may be explained by the fact that the present study enrolled mainly patients with severe symptomatic AS, whereas the population of the study by Bull et al 31 also involved asymptomatic patients with moderate to severe AS. Several authors post-contrast administration showed high accuracy to identify patients with severe DMF.…”
Section: Myocardial Fibrosis Vs LV Morphology and Functionmentioning
confidence: 50%
“…Bull et al have shown a moderate but significant correlation between the native T1 relaxation time and DMF in 19 patients with severe symptomatic AS using the ShMOLLI (a shortened MOLLI) sequence with a 1.5-T scanner. 31 Lee et al have even shown a strong correlation between the native T1 relaxation time and DMF in 20 patients with severe AS using a 3-T scanner and the MOLLI sequence. 21 De Meester de Ravenstein et al 22 have shown the opposite result.…”
Section: T1 Mapping Vs Diffuse Myocardial Fibrosismentioning
confidence: 99%
“…It demonstrated that the precontrast "native T1" has a linear correlation with the percentage of myocardial fibrosis as measured histologically on invasive myocardial biopsy. T1 times postcontrast administration (10-15 min) had an inverse linear relationship with collagen content in myocardial fibrosis subjects [8,21,22]. …”
Section: T1 Mapping With Modified Look-locker Inversion "Molli" Recoverymentioning
confidence: 99%
“…46 T1 measures permit noninvasive detection of biologically and pathologically important processes related to excess water in edema, protein deposition, and other T1 altering substances such as lipid or iron in hemorrhage. [46][47][48][49][50] The ECV technique is sensitive to the distribution of the LV myocardium into its cellular and extracellular interstitial compartments. 47 Alterations in these compartments occurring from different physiologic and pathophysiologic biologic processes leading to fibrotic changes can be more easily detected with ECV than with LGE.…”
Section: Myocardial T1 Mapping and Extracellular Volume (Ecv) Fractionmentioning
confidence: 99%